Color Vowel Approach: Coping with Students’ Learning Styles in Teaching Pronunciation - Putri, Prisna Aswarita; Adawiah, Rabiatul (Yayasan Pendidikan Bima Berilmu, 2024)
The objective of this study was to probe how to provide a teaching method which accommodates learning styles preferred by students and boost their learning achievement in Pronunciation Practice course by using Color Vowel approach. This qualitative research was conducted at the English Education study program of Islamic State University Datokarama Palu where second semester students were taken as participants. Data gathered from pre-research survey, field notes, questionnaire, and mid-term test result analysis showed that a significant correlation between the use of Color Vowel approach and students’ learning achievement in Pronunciation Practice course was undeniable. It helped the students to easily comprehend material being taught as well as yielded a relaxed learning environment where students could learn best.